A genome-wide association study with 1,126,563 individuals identifies new risk loci for Alzheimer’s disease - Wightman, Douglas P.; Jansen, Iris E.; Savage, Jeanne E.; Shadrin, Alexey A.; Bahrami, Shahram; Holland, Dominic; Rongve, Arvid; Børte, Sigrid; Winsvold, Bendik S.; Drange, Ole Kristian; Martinsen, Amy E.; Skogholt, Anne Heidi; et al. (Nature genetics, 2021)
Late-onset Alzheimer’s disease is a prevalent age-related polygenic disease that accounts for 50–70% of dementia cases. Currently, only a fraction of the genetic variants underlying Alzheimer’s disease have been identified. Here we show that increased sample sizes allowed identification of seven previously unidentified genetic loci contributing to Alzheimer’s disease. This study highlights microglia, immune cells and protein catabolism as relevant to late-onset Alzheimer’s disease, while identifying and prioritizing previously unidentified genes of potential interest. We anticipate that these results can be included in larger meta-analyses of Alzheimer’s disease to identify further genetic variants that contribute to Alzheimer’s pathology. A genome-wide association study performed in 1,126,563 individuals identifies seven new loci associated with Alzheimer’s disease and implicates microglia and immune cells in late-onset disease.